ISOLASI, IDENTIFIKASI DAN KARAKTERISASI PENYEBAB PENYAKIT KARAT DAUN PADA SEMAI PINUS DI PERUM PERHUTANI BKPH PURWOREJO, KPH KEDU SELATAN - Nur Hidayati; Siti Husna Nurrohmah; Fithry Ardhany (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
Pinus merkusii, a multiuse tree, is cultivated at Indonesian Plantation. Pinus plantation have been threatened by rust/spot leaf disease. The pathogen has infected pinus seedlings at Perum Perhutani, BKPH Purworejo, KPH Kedu Selatan and cause high mortality. The aims of this research to identify pathogen causing rust/spot leaf thus information how to control can be observed. Pathogens were isolated from infected leaves, and grown on the potato dextrose agar (PDA) and observed macroscopis and microscopis and identified. The pathogens also were inoculated to healthy seedlings (Postulat Koch Test). The result shows that pathogen causing rust/spot leaf on seedlings pine is Pestalotia sp with characteristic white colony, hypha has aservuli with conidia that have 25 septums and at the edge, some structure looks like feather whipped 3-5. Potulat Koch test indicated that inoculated healthy seedling shows similar symptom with infected seedlings. Rust/spot leaf has similar sympto and sign. Spot or rust appear on leaves started from edge and spread to base. At first, spots were formed in small size and separate each other but they developed and became larger and wider and fused.